Gut Microbiota as an Objective Measurement for Auxiliary Diagnosis of Insomnia Disorder - Liu, Bingdong; Lin, Weifeng; Chen, Shujie; Xiang, Ting; Yang, Yifan; Yin, Yulong; Xu, Guohuan; Liu, Zhihong; Liu, Li; Pan, Jiyang; Xie, Liwei (Frontiers in Microbiology, 2019)
Insomnia is a type of sleep disorder, which is associated with various diseases development and progression, such as obesity, type II diabetes and cardiovascular diseases. Recent investigation of gut-brain axils enhances our understanding of the role of gut microbiota in brain-related diseases. However, whether gut microbiota is associated with insomnia remains unknown. In the present investigation, leveraging on the 16S rDNA amplicon sequencing of V3-V4 region and the novel bioinformatic analysis, it was demonstrated that between insomnia and healthy population, the composition, diversity and metabolic function of gut microbiota are significantly changed. Other than these, the redundancy analysis, co-occurrence analysis and PICRUSt underpin the gut taxa composition, signaling pathways, and metabolic functions perturbed by insomnia disorder. Moreover, random forest together with cross-validation identified two signature bacteria, which could be used to distinguish the insomnia patients from healthy population. Furthermore, based on the relative abundance and clinical sleep parameter, we constructed a prediction model utilizing Artificial Neural Networks (ANN) for auxiliary diagnosis of insomnia disorder. Overall, the aforementioned study provides a comprehensive understanding of the link between gut microbiota and insomnia disorder.